Property Market Purpose Efficiency: An Exploratory Analysis From an Institutional Economics Perspective - Paschalis Arvanitidis (European Regional Science Association (ERSA), 2006)
Over the last years the issue of property market efficiency has attracted increasing attention in both academic and professional research. Yet, the concept of property market efficiency is poorly developed and inadequately theorised. The conventional approaches (i.e. 'allocative efficiency' and 'efficient market hypothesis') provide flawed and ambiguous judgements as they assess efficiency with reference to idealised benchmarks, they do not take into account the intrinsic characteristics and dynamic process of the property market and they are artificially dissociated from important operational issues. In turn, institutionalist attempts to articulate more refined and pragmatic conceptualisations of property market efficiency, while they have provided useful insights, remain methodologically underdeveloped and incomplete. Building on the latter approaches the current paper explores a possible way to evaluate the effectiveness of the property market in delivering a combination of outcomes that will generate and/or sustain urban economic development. This provides the basis for the development of the idea of a 'purpose efficient property market'. To achieve this, two theoretical devices are developed: 'institutional uncertainty' and 'institutionalised variety'. Institutional uncertainty assesses the quality of the wider (urban) institutional arrangements and reflects how effectively the urban socioeconomy adapts to pressures and provides a secure economic environment. Institutionalised variety evaluates particular institutions, in this case the property market, in terms of diversity in institutions, organisations, and products provided. Such a micro-level variety is deemed necessary both for the system to reproduce itself through time and for macro dynamics to be successfully sustained. In that sense, macroeconomic order and relative stability are reinforced alongside, and arise upon, variety and diversity at the micro-level. Putting the arguments together, the property market purpose efficiency is understood with reference to the market's ability to match 'institutionalised variety' to the level of 'institutional uncertainty' that the wider urban institutional environment exhibits. In that sense, a purpose efficient property market allocates optimal resources to institutionalised variety, given the level of uncertainty the wider institutional environment carries, and thereby delivers the property products that the economy requires at the prevailing price.
Keywords: 330